التسويق الأخضر كمدخل للحماية البيئية في ضوء المسئولية الاجتماعية للمنظمات بأبعادها الاقتصادية والاجتماعية- الإشارة إلى حالة شركتيdell و Ibm - بياض, مصطفى; عبد الجبار, سهيلة (جامعة الوادي - University of Eloued, 2022)
green marketing sees as a translation of the social and ethical responsibility requirements for marketing, which have come to light in response to today's growing environmental challenges .and this approach to marketing coming in step with the growing global interest in protection environment, and the emergence of movements to protect the rights of people to live in an environment focused on organizing a clean and safe environment. Indeed green marketing focuses on the commitment of business organizations to the production of environmentally friendly products that represent products that are harmless to society and the natural environment, and to practice marketing activities within the framework of 'a strong commitment to environmental responsibility and to specific controls to ensure the preservation of the natural environment. This is what we are trying to highlight through this research paper by studying the case of DELL and IBM.
Green marketing as an approach to environmental protection in light of the social responsibility of organizations with its economic and social dimensions - reference to the case of DELL and IBM
مقال
Keywords: التسويق الأخضر، المسؤولية الاجتماعية والأخلاقية، إدارة المخلفات،مواصفات الإيزو، الحماية البيئية.; Green marketing, social and ethical responsibility, waste management, ISO standards, environmental protection.